2009
DOI: 10.1038/jes.2009.9
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase status and plasma butyrylcholinesterase activity in chlorpyrifos manufacturing workers

Abstract: Chlorpyrifos is an organophosphorus (OP) anticholinesterase insecticide. Paraoxonase (PON1) is an enzyme found in liver and plasma that hydrolyzes a number of OP compounds. PON1 polymorphisms include a glutamine (Q)/arginine (R) substitution at position 192 (PON1 Q192R ) that affects hydrolysis of OP substrates, with the PON1 192Q allotype hydrolyzing chlorpyrifos oxon less efficiently than the PON1 192R allotype, a variation potentially important in determining susceptibility to chlorpyrifos. We studied 53 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
2
14
1
1
Order By: Relevance
“…Plasma samples contained all functional phenotypes of PON1, and the majority was represented by QQ, the phenotype with the lowest CPFoxon hydrolysis activity. The functional phenotype ratio measured here was similar to those reported previously (Albers et al, 2010;Davis et al, 2009), and adult oxon hydrolysis rates were comparable to what others have reported in the literature .…”
Section: Smith Et Alsupporting
confidence: 79%
“…Plasma samples contained all functional phenotypes of PON1, and the majority was represented by QQ, the phenotype with the lowest CPFoxon hydrolysis activity. The functional phenotype ratio measured here was similar to those reported previously (Albers et al, 2010;Davis et al, 2009), and adult oxon hydrolysis rates were comparable to what others have reported in the literature .…”
Section: Smith Et Alsupporting
confidence: 79%
“…In contrast to these findings, however, in workers involved in the manufacturing of chlorpyrifos and exposed to this OP, the decreased plasma BuChE activity was not associated with low PON1 status (Albers et al 2010). …”
Section: Introductioncontrasting
confidence: 66%
“…This is consistent with the reported insensitivity of AChE activity to exposures to OP pesticides that are far below lethal levels. A study in workers involved in the manufacturing of chlorpyrifos found that the decreased AChE activity was not associated with low PON1 status (Albers et al 2010). Similarly, a study in agricultural workers observed inhibition of AChE and BChE after chlorpyrifos application but an association of PON1 activity with inhibition was not found (Ellison et al 2012).…”
Section: Discussionmentioning
confidence: 99%